2014
DOI: 10.2478/s11532-014-0570-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure and capacitive properties of cobalt hydroxide films on stainless steel substrates

Abstract: Cobalt (hydro)oxide films on AISI 304 stainless steel and sintered metal fibre filter Bekipor ST 20AL3 were prepared using electrochemical deposition from neutral cobalt acetate solutions under galvanostatic conditions. Deposited films were structurally characterized using X-ray diffraction, Fourier transform infrared spectroscopy and scanning electron microscopy. All electrochemical measurements were performed in aqueous NaOH solution. Capacitive behavior of different films was evaluated using cyclic voltamme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…3a) was measured using the same ferro-ferricyanide oxidation-reduction system. Cobalt oxide Co 3 O 4 , as well-known material for its electrocatalytic activity [6,8,13,[33][34][35] in oxygen evolution reaction, was obtained during heat treatment of as-deposited Co(OH) 2 coatings at 673 K for 1 h. The lamellar structure and composition of tricobalt tetraoxide was confirmed in previous studies [23] by XRD, FTIR and XPS. In order to investigate the effect of temperature treatment to electroactive surface area, the same measurements as with Co(OH) 2 were performed (Fig.…”
Section: Determination Of Electroactive Surface Areasupporting
confidence: 48%
See 4 more Smart Citations
“…3a) was measured using the same ferro-ferricyanide oxidation-reduction system. Cobalt oxide Co 3 O 4 , as well-known material for its electrocatalytic activity [6,8,13,[33][34][35] in oxygen evolution reaction, was obtained during heat treatment of as-deposited Co(OH) 2 coatings at 673 K for 1 h. The lamellar structure and composition of tricobalt tetraoxide was confirmed in previous studies [23] by XRD, FTIR and XPS. In order to investigate the effect of temperature treatment to electroactive surface area, the same measurements as with Co(OH) 2 were performed (Fig.…”
Section: Determination Of Electroactive Surface Areasupporting
confidence: 48%
“…The electrodeposition process was carried out under galvanostatic conditions. The previously obtained results [23] showed that the most stable films were obtained at 0.5 mA/cm 2 . Temperature treatment for all deposited coatings was carried out in 673 K for 1 h; temperature raising speed was 10 K min…”
Section: Experimental Preparation Of the Filmsmentioning
confidence: 57%
See 3 more Smart Citations